2009
DOI: 10.1007/s12206-009-0733-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the influence of labyrinth seal configuration on leakage behavior

Abstract: This study analyzed the influence of configuration and clearance on the leakage behavior of labyrinth seals. Both computational fluid dynamics (CFD) and an analytical tool were used to predict the leakage flow of two different (straight and stepped) seal configurations with various clearances. The predicted results were compared with experimental data. The CFD gives a better agreement with the experimental result than the analytical model on average. In the straight seal, the dependence of the discharge coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 12 publications
4
51
0
Order By: Relevance
“…It is a dimensionless quantity and is often used to describe the sealing efficiency [7,[16][17][18][19][26][27][28][29]:…”
Section: Discharge Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a dimensionless quantity and is often used to describe the sealing efficiency [7,[16][17][18][19][26][27][28][29]:…”
Section: Discharge Coefficientmentioning
confidence: 99%
“…Suryanarayanan and Morrison [16][17][18] studied the relationship between the flow coefficient and transmission coefficient inside the labyrinth channels in detail, and the influence of the tooth type, compression ratio, clearance, and Reynolds number were obtained. Kim and Cha [19] combined the computational fluid dynamics (CFD) method and a theoretical analysis to discuss the influence of the structural arrangement and pressure ratio on the sealing efficiency and found that a stepped labyrinth seal is more efficient when the labyrinth clearance is larger. Bozzi et al [20] performed a more detailed analysis on the heat transfer in a labyrinth seal.…”
Section: Introductionmentioning
confidence: 99%
“…However, this structure has an inherent problem of leakage, which deteriorates the volumetric efficiency of the pump seriously [4] . The labyrinth seal featured by noncontacting structure has been widely used in rotating machines for dynamic seal over the years [5][6][7][8] . In marine environment, however, the labyrinth seal shows the benefits of low maintenance and reduced particulate contamination.…”
Section: Introductionmentioning
confidence: 99%
“…For example, straight-through seals [6,8,9] , stepped seals [1,6,10] , honeycomb seals [10][11][12][13] , interlocking seals [1,14,15] have different sealing performance. Furthermore, the structural parameters of cavities also influence the leakage of labyrinth seals, such as cavity width, cavity depth, cavity numbers and clearance size, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The less is the number of labyrinth seals, the greater is the leakage amount because of the number of steam seal teeth; moreover, the leakage amount increases with an increase in seal tip clearance [10] [11]. On this basis, a researcher pointed out that the leakage coefficient is linear to the sealing tip clearance [12].…”
Section: Introductionmentioning
confidence: 99%